Quantitative Determination of Flavonoids and Chlorogenic Acid in the Leaves of Arbutus unedo L. Using Thin Layer Chromatography - Željan Maleš; Darija Šarić; Mirza Bojić (Journal of Analytical Methods in Chemistry)
The plant species Arbutus unedo shows numerous beneficial pharmacological effects (antiseptic, antidiabetic, antidiarrheal, astringent, depurative, antioxidant, antihypertensive, antithrombotic, and anti-inflammatory). For the medicinal use, standardization of extracts is a necessity, as different compounds are responsible for different biological activities. In this paper, we analyze monthly changes in the content of quercitrin, isoquercitrin, hyperoside, and chlorogenic acid. Methanolic extracts of the leaves are analyzed by HPTLC for the identification and quantification of individual polyphenol, and DPPH test is used to determine antioxidant activity. Based on the results obtained, the leaves should be collected in January to obtain the highest concentrations of hyperoside and quercitrin (0.35 mg/g and 1.94 mg/g, resp.), in June, July, and October for chlorogenic acid (1.45–1.46 mg/g), and for the fraction of quercitrin and isoquercitrin in November (1.98 mg/g and 0.33 mg/g, resp.). Optimal months for the collection of leaves with the maximum recovery of individual polyphenol suggested in this work could direct the pharmacological usage of the polyvalent herbal drugs.